Evolutionary dynamics of Hepatitis C virus in a chronic HIV co-infected patient and its correlation with the immune status - Culasso, Andrés Carlos Alberto (2018)
The HCV evolutionary dynamics play a key role in the infection onset, maintenance of chronicity, pathogenicity, and drug resistance variants fixation, and are thought to be one of the main caveats in the development of an effective vaccine. Previous studies in HCV/HIV co-infected patients suggest that a decline in the immune status is related with increases in the HCV intra-host genetic diversity. However, these findings are based on single point sequence diversity measures or coalescence analyses in several virus-host interactions. In this work, we describe the molecular evolution of HCV-E2 region in a single HIV-co-infected patient with two clearly defined immune conditions. The phylogenetic analysis of the HCV-1a sequences from the studied patient showed that he was co-infected with three different viral lineages. These lineages were not evenly detected throughout time. The sequence diversity and coalescence analyses of these lineages suggested the action of different evolutionary patterns in different immune conditions: a slow rate, drift-like process in an immunocompromised condition (low levels of CD4+ T lymphocytes); and a fast rate, variant-switch process in an immunocompetent condition (high levels of CD4+ T lymphocytes).